Sitotoksisitas in vitro ekstrak etanolik buah parijoto (Medinilla speciosa, reinw.ex bl.) terhadap sel kanker payudara T47D - Tusanti, Iin; Johan, Andrew; Kisdjamiatun, RA (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2014)
Background: Several studies focused on phytochemical as agents of cancer prevention and co-chemotherapy. One of Indonesian plant which has edible fruit but it hasn’t been completely explored is Medinilla speciosa (Reinw.ex Bl.). Objective : The aim of this study is to examine the cytotoxic activity (IC50 value) of Medinilla speciosa (Reinw.ex Bl.) fruit ethanolic extract. Methods : Medinilla speciosa (Reinw.ex Bl.) fruit ethanolic extract was used in this study. The cytotoxic activity was investigated in vitro on human breast cancer T47D cell-line. The cells viability were assessed using MTT colorimetric assay. Breast cancer T47D cell lines was treated with fruit ethanolic extract (10, 25, 50, 100, 250, 500 and 1000 µg/ml) for 24 hour of incubation. This study also identified phytochemical compound of the fruit with thin layer chromatography (TLC). Results: The result showed that ethanolic extract of Medinilla speciosa (Reinw.ex Bl.) has moderate cytotoxicity on breast cancer T47D cell line with IC50 value of 614.50 µg/ml and yield the decrease of cell viability at higher concentration. Medinilla speciosa fruit can not be used as anticancer agent but chemoprevention agent. Phytochemical test showed that the fruit extract contain flavonoid and saponin compound. Conclusion: Ethanolic extract of Medinilla speciosa fruit exhibited moderate cytotocicity on breast cancer T47D cell lines with IC50 value was 614,50 µg/ml thus it can be used as chemopreventioan agent.